Empowering Self-directed Learners Through Digital Innovation and Open Educational Practices - Dorothy Laubscher; Chantelle Bosch; Marry Mdakane; Ahmed Tlili; Byron John Bunt, Jane Yau; Lezeth van der Walt; Obakeng Molokwane; Nhlanhla Mbele; Lance Bunt; James Sibanda; Christo Johannes Els; Albert Kemp; et al. (AOSIS, 2025)
Empowering self-directed learners through digital innovation and open educational practices explores the interplay between self-directed learning (SDL), open educational practices (OEPs) and digital innovation in education. It represents an academic contribution to the field of education, specifically addressing the transformative potential of OEPs and digital technologies in fostering SDL. By exploring these aspects, it contributes to the scholarly discourse on integrating SDL into digital and open learning environments, thereby supporting the advancement of research and practice in these domains. The chapters collectively explore how SDL can be supported and enhanced through OEPs and digital innovation. The book incorporates a variety of research methodologies, including a literature review, a systematic literature review, theory synthesis and both quantitative and qualitative research. These diverse methodological lenses provide a robust analysis of the topic, ensuring the work contributes original, evidence-based insights to the academic community. The unique contribution of Empowering self-directed learners through digital innovation and open educational practices lies in its detailed exploration of how OEPs and digital innovation promote SDL, presenting novel frameworks, strategies and guidelines for educators, facilitators and researchers. By emphasising the practical and theoretical implications of these intersections, the book addresses critical gaps in existing research while aligning with Sustainable Development Goals (SDGs) 4 and 9. Specifically, the focus on fostering inclusive and equitable education to support lifelong learning (SDG 4), while the strategic application of digital technologies to improve teaching efficiency and transform educational practices, addresses innovation and infrastructure goals (SDG 9). The target audience includes higher education researchers, academics, educators and postgraduate students specialising in SDL, OEPs and digital innovation in education. By addressing this specialised audience, the book remains firmly within the scholarly domain, advancing academic discussions and providing actionable insights for future research and practice.